Algorithmic Skeletons and Parallel Design Patterns in Mainstream Parallel Programming - Danelutto, Marco; Mencagli, Gabriele; Torquati, Massimo; González–Vélez, Horacio; Kilpatrick, Peter (International journal of parallel programming, 2021)
This paper discusses the impact of structured parallel programming methodologies in state-of-the-art industrial and research parallel programming frameworks. We first recap the main ideas underpinning structured parallel programming models and then present the concepts of algorithmic skeletons and parallel design patterns. We then discuss how such concepts have permeated the wider parallel programming community. Finally, we give our personal overview—as researchers active for more than two decades in the parallel programming models and frameworks area—of the process that led to the adoption of these concepts in state-of-the-art industrial and research parallel programming frameworks, and the perspectives they open in relation to the exploitation of forthcoming massively-parallel (both general and special-purpose) architectures.